2021
DOI: 10.1093/cercor/bhab016
|View full text |Cite
|
Sign up to set email alerts
|

Children with Cerebral Palsy Have Altered Occipital Cortical Oscillations during a Visuospatial Attention Task

Abstract: Dynamically allocating neural resources to salient features or objects within our visual space is fundamental to making rapid and accurate decisions. Impairments in such visuospatial abilities have been consistently documented in the clinical literature on individuals with cerebral palsy (CP), although the underlying neural mechanisms are poorly understood. In this study, we used magnetoencephalography (MEG) and oscillatory analysis methods to examine visuospatial processing in children with CP and demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…In fact, visual dysfunction is now recognized as a core, co-occurring disorder affecting between 50% and 90% of individuals with CP [46][47][48][49]. This is also consistent with our previous works in MEG showing that children with CP had weaker cortical oscillations in the visual MT/V5 cortices and occipital cortices [6][7][8]. The altered connectivity seen between the motor and visual cortices might be partially a result of the white matter damage often seen in the peritrigonal region, as the optic radiation fibers are neighbors to the corticospinal tracts in this area [50].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In fact, visual dysfunction is now recognized as a core, co-occurring disorder affecting between 50% and 90% of individuals with CP [46][47][48][49]. This is also consistent with our previous works in MEG showing that children with CP had weaker cortical oscillations in the visual MT/V5 cortices and occipital cortices [6][7][8]. The altered connectivity seen between the motor and visual cortices might be partially a result of the white matter damage often seen in the peritrigonal region, as the optic radiation fibers are neighbors to the corticospinal tracts in this area [50].…”
Section: Discussionsupporting
confidence: 92%
“…Another notable result of the study was the fact that the visual cortex was consistently found to be abnormally connected to the other two primary cortices (namely, the motor and auditory cortices). Both functional and structural studies have reported abnormalities related to the visual network [6][7][8]26,29] and visual tracks [30,45] in CP. Our finding supports the idea that the disconnectivity of the visual network from the other primary networks might reflect a pathophysiological mechanism leading to visual perception impairment in CP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed 240 trials of a visuospatial discrimination task (Fig. 1 , top), which has been extensively described and validated in previous work [ 12 , 14 16 , 20 , 21 , 47 ], concurrent with MEG recording. During this task, participants were seated in a magnetically shielded room and indicated the position of a grid by a right-handed button press (left = index finger; right = middle finger).…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, studies investigating electrophysiological activity (beyond VEP recordings) in relation to higher order visual processing in CVI remain limited. A recent study by verMass and colleagues (2021) investigated children with CVI associated with cerebral palsy (CP) and used magnetoencephalography (MEG) to uncover oscillatory activity associated with visuospatial processing abilities 68 . Consistent with the findings reported here, the authors found that participants with CP had weaker theta (as well as gamma) occipital activity related to impaired performance on their visuospatial processing and attention task.…”
Section: Neural Markers Of CVI and Their Potential Clinical Significancementioning
confidence: 99%